Pemberitaan Korupsi RAPBD Pejabat Provinsi Jambi: Analisis Framing Pada Jambi TV - Haisun Hafiz; Sururuddin; Dendy H Nanda (Journal of Religion and Film, 2022)
This study aims to determine the neutrality of Jambi TV in Broadcasting News in Reporting on Corruption Crimes Arrested by the Corruption Eradication Commission OTT KPK Ratification of the Jambi Province RAPBD in January-March 2018. The mass media functions as an information disseminator. Therefore the news conveyed to the public must be clear without any distortion of meaning or meaning. Jambi TV media, which has followed this case, started with a search for a hand-catching operation carried out by the Corruption Eradication Commission team. The IDR 4.7 billion found by the Corruption Eradication Committee during the sting operation was allegedly related to the discussion of the 2018 Jambi Province RAPBD. This study used a qualitative research method using the Framing Zhongdang pan and Gerald M. Kosick analysis approach. perform analysis based on four dimensions, namely, Syntax, Script, Thematic, Rhetorical. Researchers use the method used by Michel. The results of this study explain, 1). That Jambi TV framed the news on the Jambi Province RAPBD corruption case according to what was found on the ground by journalists. 2). Jambi TV's position when broadcasting the news on the Jmabi Province RAPBD corruption case, the news that was broadcast was in accordance with the pact where no one takes sides, whether it's the KPK or the RAPBD corruption suspects. During an editorial meeting. Finally, the author worships Religion, Society, Nusa and the Nation.